Conveying Artistic Values Through Fresh Floral Arrangements by “Kirana: Thai Floral Art Lab” - Pongsuwan, Kirana; Angasinha, Asst. Prof. Dr.Chatwarun (Journal of Dhamma for Life, 2025)
The objectives of this article are: 1) to study the transmission of artistic values through fresh floral arrangements by the “Kirana: Thai Floral Art Lab,” and 2) to examine the extension of learning in fresh floral art through the “Kirana: Thai Floral Art Lab.” This is a qualitative research study, with data collected through in-depth interviews with a total of 15 key informants, divided into four groups as follows: 1) students, 2) alumni of the School of Craftsmanship in the Palace (Female), 3) customers, and 4) instructors from the “Kirana: Thai Floral Art Lab.” The data was analyzed using content analysis, framed by the theory of artistic value creation. The study results indicate that there are five key value components: 1) aesthetic value, 2) social value, 3) cultural value, 4) economic value, and 5) ethical value. Regarding the extension of learning in fresh floral art, the study found that the teaching model is based on a short-course curriculum, with each course lasting five hours. Students acquire knowledge in creating floral garlands in the traditional royal style, starting from the basics of fresh floral arrangements to advanced adaptation techniques. This includes selecting flowers, understanding the nature of flowers, familiarizing themselves with tools and equipment, garland weaving, and decorating garlands such as the "Mali Orchid Garland." Students are encouraged to use their creativity or follow contemporary styles to suit different ceremonial purposes. The teaching also emphasizes conveying the artistic values of fresh flowers according to royal craftsmanship, ensuring the complete utilization of all parts of the flowers, and promoting environmental friendliness. Furthermore, students learn storage techniques and methods for preserving the flowers' freshness and beauty for a longer period. The development of these skills depends on the students’ ability to adapt and create after mastering the foundational knowledge.